MENGINTEGRASIKAN AUGMENTED REALITY (AR) DALAM MENCIPTAKAN BISNIS YANG INOVATIF DI ERA DIGITAL UNTUK MENINGKATKAN KEPUASAN PELANGGAN - Salma Nur Fadhilatil Hidayah; Erika Wulandari; Muhammad Wahyudi (CV. Denasya Smart Publisher, 2025)
Additionally, the corporate sector is undergoing simultaneous changes due to the rapid growth of digital technology. The improvement of customer experience and operational efficiency were the main areas of these adjustments. The goal of this study is to ascertain the advantages of Augmented Reality as a novel technology in relation to marketing and consumer happiness. Approaches to the potential and difficulties of augmented reality were discovered using the literature review technique in a number of business domains, including property, MSMEs, and e-commerce. Augmented reality lowers return rates for specific items, boosts trust, and enhances real-time product presentation. Notwithstanding its advantages, AR has drawbacks that should be taken into account, such expensive technology and the reaction of new users. This body of literature offers a summary of.